2006
DOI: 10.1038/sj.bjc.6603192
|View full text |Cite
|
Sign up to set email alerts
|

An approach to estimating prognosis using fractional polynomials in metastatic renal carcinoma

Abstract: We present a prognostic model for metastatic renal cell carcinoma based on fractional polynomials. We retrospectively analysed 425 metastatic renal cell carcinoma patients treated with subcutaneous recombinant cytokine-based home therapies in consecutive trials. In our approach, we categorised a continuous prognostic index produced by the multivariable fractional polynomial (MFP) algorithm, using a strategy in which continuous predictors are kept continuous. The MFP algorithm selected five prognostic factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Overall, our results illustrate potentially serious clinical and research implications of imposing these assumptions a priori, which may lead to a failure to identify important prognostic factors, such as albumin in our study, inaccurate identification of high-risk groups, or spurious contradictions between the results of short-vs long-term prognostic studies. These results are in line with several other clinical and methodological studies indicating important violations of PH and/or linearity hypotheses (Ramsay, 1988;Sleeper and Harrington, 1990;Hastie and Tibshirani, 1990;Royston and Altman, 1994;Greenland, 1995;Rothman et al, 1995;Abrahamowicz et al, 1997;Benedetti and Abrahamowicz, 2004;Royston et al, 2006;Spix et al, 2008). The PH assumption can be tested with simple parametric or non-parametric tests available in a standard statistical software packages (Wei, 1984).…”
Section: Discussionsupporting
confidence: 65%
“…Overall, our results illustrate potentially serious clinical and research implications of imposing these assumptions a priori, which may lead to a failure to identify important prognostic factors, such as albumin in our study, inaccurate identification of high-risk groups, or spurious contradictions between the results of short-vs long-term prognostic studies. These results are in line with several other clinical and methodological studies indicating important violations of PH and/or linearity hypotheses (Ramsay, 1988;Sleeper and Harrington, 1990;Hastie and Tibshirani, 1990;Royston and Altman, 1994;Greenland, 1995;Rothman et al, 1995;Abrahamowicz et al, 1997;Benedetti and Abrahamowicz, 2004;Royston et al, 2006;Spix et al, 2008). The PH assumption can be tested with simple parametric or non-parametric tests available in a standard statistical software packages (Wei, 1984).…”
Section: Discussionsupporting
confidence: 65%
“…In our study, lung metastasis was found in 61.3% (73/119) patients and was controlled with targeted therapy. With respect to bone metastasis, previous studies have shown mixed results, with bone metastasis identified as a significant prognostic factor in some but not all analyses; 4,15,[21][22][23] however, our study identified bone metastasis as a significant prognostic factor for OS (p < 0.05). The presence of liver or pancreas metastasis was identified as a significant prognostic predictor of shorter OS (p < 0.05).…”
Section: Prognostic Factors For Mrcc In Targeted Therapycontrasting
confidence: 48%
“…The disadvantages of this approach, related to multiple testing and generalizability of the results, have been abundantly discussed in the literature [15,16,[21][22][23]. Alternative strategies to dichotomization, in which continuous predictors are kept continuous and trends are investigated, have been proposed: among these, the most commonly used are fractional polynomials and spline regression models [23][24][25][26][27][28]. When using the restricted cubic spline regression method [24,25], we observed a significant nonlinear increase in risk of both progression and death with increasing number of CTCs; this increase rate lessened after approximately 5 CTCs.…”
Section: Discussionmentioning
confidence: 99%